THE EXTRACT OF FENNEL FRUIT AS A POTENTIAL NATURAL ADDITIVE IN FOOD INDUSTRY - Rajić, Jasmina; Đorđević, Sofija; Tešević, Vele; Živković, Marijana; Đorđević, Neda; Paunović, Dragana; Nedović, Viktor; Petrović, Tanja (Journal of Agricultural Sciences (Belgrade), 2018)
In this study polyphenol profile and antioxidant activity of hydro-ethanolic extract of fennel fruit were examined in order to investigate the possibility of its application as a potential functional food additive. Total phenols were analyzed by the method of Folin-Ciocalteu, while total flavonoids were determined by colorimetric method with aluminum chloride. The separation and quantification of phenolic compounds were performed by LC-MS/MS analysis, with multiple reactions monitoring mode (MRM). The antioxidant capacity was determined by FRAP and DPPH assay. The high values of total phenolics and flavonoids were found, as well as high antioxidant activity which amounted 9023.33 ± 38.19 µmol Fe(II)/l and 3.73 ± 0.04 mmol TE/l, tested by FRAP and DPPH assays, respectively. Among the identified phenolic compounds, p-hydroxybenzoic acid and chlorogenic acid were detected as predominant. The obtained results indicated that the hydro-ethanolic extract of fennel fruit can be used in food industry as a potential natural antioxidant.
Keywords: Flavonoids; antioxidative; phenols; extracts; Fennel; antioxidative activity